Catálogos de editoras de literatura infanto-juvenil : uma leitura - Marina Gontijo Santos Teixeira (2011)
This research, undertaken within the field of Education and Language, focused on the study of Literature and Readers Development through the analysis of publishers catalogs dedicated to children and youths literature, with intent to approach a better understanding of how schools elect the literature books they assign to their students. The relevance of this study consists in the fact that publishers catalogs play a decisive roll in the election of the literature books used in schools. For the proposed analisys 8 publishers catalogs were selected among a universe of 240. In general, the selected publishers catalogs are dedicated exclusively to children and youth's literature, do not participate in the market of textbooks and were selected for the National School Library Program (PNBE) in the year of 2010. In this study some aspects were analyzed: For wich readers are the catalogs designed? To whom are they intended? Is the publishers purpose merely commercial or is there any intention to evoke the pleasure, fantasy and unusual of Literature? Which visual or textual elements do the catalogs use to draw the reader's attention? Those questions were answered with the method of Documental Analysis, that treats the publishers catalog as a primary source of research; with the French theory of Discourse Analysis, that seeks to understand the language as socio- psychological pattern rather than a text structure and that studies the reading practices, especially through the studies of Roger Chartier which also helps us to comprehend the text marks that lead our reading. It was found that the spread of publishers catalogs among schools grew as the relationship between the Market and the Government became stronger. The research also revealed that age group is one of the main criteria used to select books in catalogs, that the readers mediators (educators) are usually seen as incapable of making literary judgment of the books and, finally, that the prizes awarded by the books is the main tool to attract customers. This study therefore aimed to broaden the understanding of Literature in schools through publishers' catalogs.